Dukungan Penafsiran Sufistik al-Qur’an terhadap Emotional Spiritual Quotient (ESQ) - Thoriqul Aziz; Ahmad Zainal Abidin (ILMU USHULUDDIN, 2019)
In classical Sufistic interpretation, it was taught about how to cultivate one's heart. This is done so that a servant can interact directly with Him. While in the modern world today it is taught about the Emotional Spiritual Quotient (ESQ) which incidentally has the same basis in the management of "emotion" and "heart" as a means to achieve success in the world and the hereafter. Between Sufistic interpretation and ESQ there is a close relationship. By using descriptive-analytical methods, this article finds that Sufistic interpretation has direction, orientation and goals that are in line with ESQ. Sufistically, there is a Qur'anic interpretation that can be used as a medium to increase emotional and spiritual skills (ESQ). In the context of Sufism practices, a very real contribution is found that one's level of religiousness is in line and closely related to one's ESQ.